Analyzing user behaviour and page views based on visitor traffic in kolej universiti poly-tech MARA website using google analytic / Mohamed Ghazali Khairuzzaman … [et al.] - Khairuzzaman, Mohamed Ghazali; Othman, Shuhadah; Adnan, Rukhiyah; Ismail, Noraini (Universiti Teknologi MARA, 2020)
The approach of the Internet has affected organizations in numerous features. The website has become an integral part of the organizations, from publicizing the organization's profile to giving web services. This study is to evaluate and analyze user behaviour pattern at Kolej Universiti Poly-Tech MARA (KUPTM) website using Google Analytics (GA) as one of the web analytic tools. Website design and its services have become a crucial part for Higher Education Institutions (HEIs) to attract users in visiting their website. Therefore, the use of web analytic tools can be an effective solution in measuring, analyzing and identifying the traffic sources for a website. Google tag was added to all KUPTM’s website and the measurement periods has been done between May 2019 and October 2019. Results have shown that the number of visitors is significantly higher during the weekdays and are affected by external stimulus. An external stimulus, such as promotional activities would increase the number of website visitors. The visit trends show weekly fluctuation in the numbers. It records high numbers of visits during the weekdays and fewer visitors during the weekend. The fluctuation could be due to the number of visits were from internal users, i.e. KUPTM employees and students. The capability of Google Analytics to analyze website traffics in terms of collecting data regarding page views, user interaction flow and visitor behaviour will benefit the organization for making a decision.